Highly efficient morpholine-based organocatalysts for the 1,4-addition reaction between aldehydes and nitroolefins: an unexploited class of catalysts - Vaghi, Francesco; Facchetti, Giorgio; Rimoldi, Isabella; Bottiglieri, Matteo; Contini, Alessandro; Gelmi, Maria Luisa; Bucci, Raffaella (Frontiers in Chemistry, 2023)
Many studies have demonstrated how pyrrolidine nucleus is more efficient than the corresponding piperidine or morpholine as organocatalysts in the condensation of aldehydes with electrophiles via enamine. Focusing on morpholine-enamines, their low reactivity is ascribed to the presence of the oxygen on the ring and to the pronounced pyramidalization of nitrogen, decreasing the enamine nucleophilicity. Thus, the selection of efficient morpholine-organocatalysts appears a strong challenge. Here, we report on the synthesis of new organocatalysts belonging to the class of β-morpholine-amino acids, that were tested in a model reaction, i.e. 1,4-addition reaction of aldehydes to nitroolefins. Starting from commercially available amino acids and epichlorohydrin, we designed an efficient synthesis of the above catalysts, controlling the configuration and the substitution pattern. Computational studies indeed disclosed the transition state of the reaction, explaining why, despite of all the limitations of the morpholine ring for enamine catalysis, our best catalyst works efficiently, affording the condensation products in excellent yields and diastereoselection and in good to exquisite enantioselectivity